Use of Electronic Resources Before and During the Pandemic in the Universitas Indonesia Library - Aswinna, Aswinna; Rahmi, Rahmi (Record and Library Journal, 2021)
Background of the study: COVID-19 impacts library activities. However, previous studies have not analysed the use of electronic resources (online database) before and during the pandemic, especially concerning higher education libraries in Indonesia. Purpose: This study investigated electronic collections before (2019) and during the pandemic (2020) in the Universitas Indonesia Library. Method: This study used a quantitative approach with descriptive analysis. Using online database usage logs from 2019 to 2020. Findings: The study divided its online database comparisons into several clusters, including multi-disciplinary, health, science and technology, and social science and humanities. The findings show that the use of almost all electronic collections declined in 2020, especially the use of e-books and protocol collections. When grouped according to knowledge clumps, however, the use of electronic collections increase in 1) health and 2) social sciences and humanities. Use declined in 1) multi-disciplinary and 2) science and technology clusters. Conclusion: This study recommends further research.